Caracterización del Sistema de Tenencia y Perfil Hematológico -Bioquímico de la Gallina Criolla Ecuatoriana en la Provincia de Cotopaxi. - Quinatoa Chicaiza, Adriana Estefania (2019)
The present study aims to characterize the possession system and the hematological-biochemical profile of the Ecuadorian free range chicken in the Cotopaxi province, performed in Sigchos, La Maná and Pangua, cantons, due to the limited information on the subject. To characterize the possession system 100 surveys were applied to the owners, the main aspects taken into account were general data on the exploitation, human resources, management of the free range chicken and health. For the Hemato-chemical, 30 blood samples were collected (15 hens and 15 roosters) with ages between 8-12 months; the hematological variables were evaluated (hematocrit, hemoglobin, erythrocytes, VGM, MCH, CGMH, platelets, leukocytes, relative and absolute values), and the biochemical profile (glucose, urea, BUN, creatinine, total proteins, AST, ALT, calcium phosphorus and potassium) with the data obtained an analysis of variance (ANOVA) was established. The free range chicken are found in different rural areas of the province of Cotopaxi, the population under study is dedicated to the backyard rearing of birds in an extensive way, where women predominate with 64%, have an average age of 48 years and their level of study is lower. The average population of Creole hens is divided in stages: 44.35% occupy the hens, followed by 35.23% of the chickens and 20.42% corresponds to the roosters, besides they do not apply a vaccination calendar and deworming The average values of the hematological and biochemical parameters of the free range chickens in the sex factor did not show an evident differentiation between females and males, in the variables; hematocrit (H 42.09 ± 2.16b) - (M35, 66 ± 2.16a) and Hemoglobin (H 13.40 ± 0.69b) - (M 11.28 ± 0.69a) if significant difference was found In favor of the females, the Tukey method was performed at 0.05% using the statistical software InfoStat. In conclusion, the data obtained in the study are in the referential ranges determined for the species in comparison with studies of other creole breeds.